Pharmacokinetics of orally administered tramadol in Muscovy ducks (Cairina moschata domestica). Issue 4 (17th January 2019) - Bailey, Ryan S.; Sheldon, Julie D.; Allender, Matthew C.; Papich, Mark G.; Chinnadurai, Sathya K.
Abstract: This study documents the pharmacokinetics of oral tramadol in Muscovy ducks. Six ducks received a single 30 mg/kg dose of tramadol, orally by stomach tube, with blood collection prior to and up to 24 hr after tramadol administration. Plasma tramadol, and metabolites O ‐desmethyltramadol (M1), and N, O ‐didesmethyltramadol (M5) concentrations were determined by high‐pressure liquid chromatography (HPLC) with fluorescence (FL) detection. Pharmacokinetic parameters were calculated using a one‐compartment model with first‐order input. No adverse effects were noted after oral administration. All ducks achieved plasma concentrations of tramadol above 0.10 μg/ml and maintained those concentrations for at least 12 hr. Elimination half‐life was 3.95 hr for tramadol in ducks, which is similar to other avian species. All ducks in this study produced the M1 metabolite and maintained plasma concentrations above 0.1 μg/ml for at least 24 hr.